INCORPORATING RELIGIOUS MODERATION VALUES INTO ENGLISH LANGUAGE TEACHING: A PORTRAIT OF AN INDONESIAN VOCATIONAL SCHOOL - Sri Wahyuningsih; Anisa Munawaroh (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
ABSTRACTThe present study explores the process of instilling religious moderation values in English teaching at an Indonesian vocational school. Furthermore, challenges in instilling religious moderation values and solutions are discussed. The qualitative case study method was used in this study. Data were gathered through observation, semi-structured interviews with two English language teachers and two students at an Indonesian vocational school, and documentation. The findings reveal that internalization of religious moderation values can be incorporated through verbal stimulation (reminders and advice), English material, teaching methods, teachers' behavior, and assignments. These values include tolerance, discussion, justice, dynamics, creativity, and innovation. Meanwhile, challenges include students' personality differences and a lack of English textbooks containing religious moderation values. Several strategies were used to tackle the obstacles, including motivating students to participate actively in the teaching and learning process and exploring English material dealing with religious moderation. The implication of the study was discussed. ABSTRAKPenelitian ini bertujuan untuk mengeksplorasi proses penanaman nilai-nilai moderasi beragama dalam pengajaran bahasa Inggris di sekolah menengah kejuruan (SMK) di Indonesia. Selanjutnya, tantangan yang dihadapi guru bahasa Inggris dalam menanamkan nilai-nilai moderasi beragama, dan solusinya juga dibahas. Metode studi kasus kualitatif digunakan dalam penelitian ini. Data dikumpulkan melalui observasi, wawancara semi terstruktur dengan dua guru bahasa Inggris dan dua siswa SMK di Indonesia, dan dokumentasi. Hasil temuan menunjukkan bahwa internalisasi nilai moderasi beragama dapat diwujudkan melalui stimulasi verbal (pengingat dan nasihat), materi bahasa Inggris, metode pengajaran, perilaku guru, dan penugasan. Nilai-nilai tersebut antara lain toleransi, diskusi, keadilan, dinamika, kreativitas, dan inovasi. Guru bahasa Inggris menghadapi tantangan karena perbedaan kepribadian siswa dan terbatasnya sumber atau materi bahasa Inggris yang mengandung nilai-nilai moderasi agama. Adapun beberapa strategi yang digunakan guru untuk mengatasi kendala tersebut antara lain memotivasi siswa untuk berpartisipasi aktif dalam proses belajar mengajar dan mengeksplorasi materi bahasa Inggris yang berhubungan dengan moderasi agama. Implikasi dari temuan dibahas dalam penelitian ini.How to Cite: Wahyuningsih, S. & Munawaroh, A. (2023). Incorporating Religious Moderation Values into English Language Teaching: A Portrait of an Indonesian Vocational School. IJEE (Indonesian Journal of English Education), 10(2), 409-427. doi:10.15408/ijee.v10i2.28946.